Profil Kapasitas Aerobik Atlet Tinju Profesional Indonesia (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2007)
Objectives: The purpose of this study was to detect capacity profile aerobic that got good for evaluate to what professional fist athlete that competes good in also abroad has sta-mina jantung-paru good. Methods: By using research method to measures capacity aerobic, number that got compared normal value. Normal value for boxer that has heavy body 48 - 60 kg 65 ml/kg bb. Min, 61 - 74 kg 60 ml/kg bb. Min and on 74 kg 50 ml/kg bb. Min. heart capacity paru measuresed by astrand test, by using ergocycle monarch. Body weighing boxer 48 - 60 kg given load 150 watts, body weighing boxer 61 - 74 kg given load 200 watts and body weighing boxer on 74 kg given load 250 watts. Pedal ro-tation speed 50 rpm. Long load 5 minutes or until conditon steady state. To count heart capacity lung by compare load and latest pulse frequency in a table. Number that got compared with normal value.Keywords: Aerobic Capacity, Endurance, Resistance